Submorfotipos del primer molar superior según patrón cuspídeo del molar inferior en clase I molar (2022)
Within the craniofacial complex, the influence of dental morphology in the ideal exercise of functions such as swallowing, phonation and chewing is highlighted, mainly the role of the first molars as determining pillars, coming to be considered the key to occlusion, through establishing the type of malocclusion present (class I, II, III). This classification is directly related to the morphological variations of both the upper and lower molars.